2006
DOI: 10.1007/s10570-006-9098-4
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the nanoporosity of cellulosic fibers on their streaming potential and their interactions with cationic polyelectrolytes

Abstract: Electrokinetic tests, based on the streaming potential method, were used to elucidate interactions between cationic polyelectrolytes and cellulosic fibers and to reveal aspects of fibers' nanoporosity. The fibrillated and nanoporous nature of bleached kraft fibers gave rise to time-dependent changes in streaming potential, following treatment of the wetted fibers with polydiallyldimethylammonium chloride. Electrokinetic test results were consistent with an expected longer time required for higher-mass polyelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
(65 reference statements)
1
48
0
1
Order By: Relevance
“…The presence of lumen structure, as mentioned earlier, has been considered as a contributing factor in the secure holding of oil after its collection (Abdullah et al 2010). The mesoporous structure of a cellulosic fiber, depending on its water-swollen nature (Stone and Scallan 1966;Hubbe et al 2007), also can be expected to imbibe and hold the fluid. In other words, the oil may partly or fully replace air or water already present in the pores, within which fluids are held by capillary forces (Washburn 1921;Choi et al 1993;Adamson and Gast 1997;Ribeiro et al 2000;Inagaki et al 2002b).…”
Section: Holdup Strength or Resistance To Unintended Releasementioning
confidence: 99%
“…The presence of lumen structure, as mentioned earlier, has been considered as a contributing factor in the secure holding of oil after its collection (Abdullah et al 2010). The mesoporous structure of a cellulosic fiber, depending on its water-swollen nature (Stone and Scallan 1966;Hubbe et al 2007), also can be expected to imbibe and hold the fluid. In other words, the oil may partly or fully replace air or water already present in the pores, within which fluids are held by capillary forces (Washburn 1921;Choi et al 1993;Adamson and Gast 1997;Ribeiro et al 2000;Inagaki et al 2002b).…”
Section: Holdup Strength or Resistance To Unintended Releasementioning
confidence: 99%
“…Studies have demonstrated maximum levels of fine particle retention, the best performance of dry-strength additives, and/or the fastest dewatering rates when enough of a high-charged cationic additive was added to adjust the zeta potential close to zero (Strazdins 1977;Lindström et al 1974;Horn and Melzer 1975;Stratton and Swanson 1981;Hubbe et al 2007b). Such observations provide evidence that, at least in those cases, charge interactions can play a dominant role.…”
Section: Methods For Determining Charge Demandmentioning
confidence: 99%
“…The effects of very small pores in the cell walls of water-swollen cellulosic fibers, especially in the case of kraft pulp fibers, have become increasingly well known (Stone and Scallan 1968;Li et al 1993;Berthold and Salmén 1997;Alince and van de Ven 1997;Alince 2002;Hubbe 2006;Hubbe et al 2007b). One of the consequences of fibers' mesoporous nature is that low-mass cationic polymers tend to adsorb in greater amounts compared to their higher-mass analogues (Hostetler and Swanson 1974;Lindström and Söremark 1976;Petlicki and van de Ven 1994;Farley 1997;Taipale et al 2011).…”
Section: Fiber Mesoporosity and Its Effects On Polyelectrolyte Permeamentioning
confidence: 99%
“…The higher deposition rate for C-LPEI on cellulose compared to C-HPEI could be related to greater adsorption of LPEI on cellulose. This can be explained by the lower diffusion rate of larger polyelectrolytes into the pore spaces of cellulose, [38] which is due to steric and electrostatic interaction of larger polyelectrolytes with the pore walls. To quantitatively investigate the effect of molecular weight on the adsorption of PEI on cellulose, the decrease in concentration of PEI by immersion of equal quantities of cellulose after 5 min was investigated by UV/Vis spectrophotometry.…”
Section: Lbl Deposition On Cellulose Fibersmentioning
confidence: 99%